PERSEPSI PENDIDIK TERHADAP PELAKSAAN PENDIDIKAN AGAMA ISLAM DI MADRASYAH IBTIDAIYAH - Zuhairi, Zuhairi (P3M STAIN Jurai Siwo Metro, 2011)
Islamic Religion Education is one of the subjects that should be given in every level of education, from the lowest to the highest. All this tune, the leaching implementation of this subject are more dominated by teachers, either in directing pupils to know, to understand, to apply the norms of religion or in creating them to be both individual and social creatures. In transferring the Islamic education into tore pupil life in the form of faith, Islamic law, understanding toward reading and writing of Al-Qurâan, the use of an appropriate method and completeness of infra structure are the prime determinant in this case in order to gain desired goals.Keyword: Islamic religion education, teacher and Islamic elementary school